GADAI EMAS iB PADA PT BPD KALSEL SYARIAH CABANG KANDANGAN - NISPAN RAHMI (At-Taradhi Jurnal Studi Ekonomi, 2014)
This study aims to determine how the practices and procedures of gold pawning at BPD Kalsel Syariah Kandangan branch office and the compliance with Fatwa DSN 25/DSN-MUI/III/2002: Rahn. This research was conducted on BPD Kalsel Syariah Kandangan branch office using descriptive analysis method. Data were obtained through interviews and document research. The results of this study indicate that the gold pawning procedures through the following stages: Estimators explain in brief about BPD mortgage loan products to customers. While the contract is used is as follows: qardh contract, for the binding of loan funds provided by Sharia Bank or UUS to customers; rahn contract, for the binding of gold as collateral for the loan fund; ijarah contract, for the binding of storage utilization and maintenance services of gold as loan funds collateral.